New records of plants eaten by the tapir, Tapirus bairdii (Perissodactyla: Tapiridae) in Braulio Carrillo National Park, Costa Rica - Carvajal, Jose Pablo (2020)
We report Tapirus bairdii eating Schefflera rodriguesiana and Gunnera insignis in Volcán Barva, Costa Rica.